2015
DOI: 10.1111/bcp.12833
|View full text |Cite
|
Sign up to set email alerts
|

4β‐hydroxycholesterol correlates with dose but not steady‐state concentration of carbamazepine: indication of intestinal CYP3A in biomarker formation?

Abstract: Aim 4β‐hydroxycholesterol (4βOHC) is an endogenous CYP3A(4) biomarker, which is elevated by use of the CYP3A4 inducer carbamazepine. Our aim was to compare to what extent serum concentration of 4βOHC correlates with dose (presystemic exposure) and steady‐state concentration (systemic exposure) of carbamazepine. Methods The study was based on a therapeutic drug monitoring material, including information about daily doses and steady‐state concentrations (Css) of carbamazepine. 4βOHC concentrations were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 30 publications
(49 reference statements)
1
40
0
Order By: Relevance
“…One previous study failed to show significant associations between 4βOHC levels and clearance estimates of the CYP3A4 substrates docetaxel and paclitaxel following intravenous administration [30]. This latter might reflect potential relevance of non-CYP3A4 mechanisms in clearance of docetaxel and paclitaxel, but in light of the possible role of intestinal CYP3A4 in biomarker formation [17], the intravenous administration of these substrates could also be a factor of relevance for the reported lack of associations with 4βOHC levels in that study.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…One previous study failed to show significant associations between 4βOHC levels and clearance estimates of the CYP3A4 substrates docetaxel and paclitaxel following intravenous administration [30]. This latter might reflect potential relevance of non-CYP3A4 mechanisms in clearance of docetaxel and paclitaxel, but in light of the possible role of intestinal CYP3A4 in biomarker formation [17], the intravenous administration of these substrates could also be a factor of relevance for the reported lack of associations with 4βOHC levels in that study.…”
Section: Discussionmentioning
confidence: 58%
“…30-50% higher in females than males), which provide clear evidence that basal CYP3A4 activity is higher in females than males. The underlying mechanism for the gender difference in CYP3A4 phenotype is uncertain, but we recently observed that females appeared to be more responsive towards induction of CYP3A4 activity during use of carbamazepine [17]. The higher basal CYP3A4 activity in females than males might therefore be due to greater responsiveness towards exogenous or endogenous factors increasing enzyme activity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Plasma concentration of 4βOHC was determined by a previously described UPLC‐MS/MS assay . The lower limit of quantification was 10 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The lower limit of quantification was 10 ng/mL. Intra‐ and interday imprecision and inaccuracy for the method were <15% at 10 ng/mL and <4% at 644 ng/mL (n = 6) . All samples were stored at −80°C between sampling and analysis.…”
Section: Methodsmentioning
confidence: 99%